Becoming a clinician: Trainee identity formation within the general practice supervisory relationship. Issue 11 (24th June 2020) - Brown, James; Reid, Helen; Dornan, Tim; Nestel, Debra
Abstract: Objectives: Becoming a clinician is a trajectory of identity formation in the context of supervised practice. This is a social process where the supervisory relationship is key. Therefore, to know how to support identity formation of clinical trainees, it is necessary to understand how this happens within the supervisory relationship. Our aim was to develop a conceptualisation of trainee identity formation within the general practice supervisory relationship to aid its support. Methods: We took a critical realist approach using case study design and 'cultural worlds' theory as a conceptual frame. Each case comprised a general practice trainee and supervisor pair. Our data were weekly audiorecordings of interactions between trainee, supervisor and a patient over 12 weeks augmented by post‐interaction reflections and sequential interviews. We undertook interpretive analysis using dialogic methods focusing on the doing of language and the cultural discourses expressed. Results: We identified three social discourses centring on: clinical responsibility; ownership of clinical knowledge, and measures of trainee competency. Versions of these discourses defined four trainee‐supervisor relational arrangements within which trainee and supervisor assumed reciprocal identities. We labelled these: junior learner and expert clinician; apprentice assistant and master coach, and lead clinician and advisor. We found a trajectory across these identity arrangements. Behind this trajectory was an invitation by the supervisor to the trainee into the social space of clinician and a readiness of the trainee to accept this invitation. Congruence in supervisor and trainee positioning was important. Conclusions: In the supervisory relationship, trainee and supervisor adopted reciprocal identities. For trainees to progress to identity of 'lead clinician, ' supervisors needed to invite their trainee into this space and vacate it themselves. Congruence between supervisor positioning of their trainee and trainee authorship of themselves was important and was aided by explicit dialogue and common purpose. We offer a model and language for trainees, supervisors and departments or schools to facilitate this. Abstract : Within supervisory relationships, trainees and supervisors adopt reciprocal identities that should change over time. Brown et al. highlight actions both can take to facilitate this transition.